Pediatric Ambulatory Blood Pressure Classification: The Case for a Change. Issue 5 (4th October 2021) - Mitsnefes, Mark; Flynn, Joseph T.; Brady, Tammy; Baker-Smith, Carissa; Daniels, Stephen R.; Hayman, Laura L.; Tran, Andrew; Zachariah, Justin P.; Urbina, Elaine M.
Abstract : In 1997, Soergel et al 1 published the first set of normative values for ambulatory blood pressure monitoring (ABPM) in children. Since then, the clinical utility of ABPM has increased dramatically, and now, ABPM is accepted as the standard method to confirm the diagnosis of hypertension in children. Despite significant progress in the field of pediatric ABPM, many important questions remain unanswered. One of the most controversial issues is how to define ambulatory hypertension in children. The purpose of this review is to discuss the limitations of the current pediatric ABPM classification scheme and to provide the justification and rationale for a new classification.